KEMAMAMPUAN PEMAHAMAN GAIRAIGO PADA MAHASISWA PENDIDIKAN BAHASA JEPANG ANGKATAN 2018 FKIP UNIVERSITAS RIAU - Aditio Syafril Pratama; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on its origin, Japanese vocabulary (goi) is divided into wago, kango and gairaigo. gairaigo are words taken from foreign languages that have been included in the Japanese language system. gairaigo broadly consists of 5 types; representational, replacement, truncated, altered, and pseudo terms. Gairaigo are loan words from foreign languages that have undergone adjustments, one of which is adjustments in writing. Gairaigo is not written using romanji as in the original language but is written using katakana characters. The research approach in this study uses a quantitative descriptive research approach. This research will be carried out at the University of Riau, the Japanese Language Education Study Program, FKIP, Riau University, class 2018. The sample of this research was 24 students of the Japanese Language Education Study Program, Riau University, class 2018. The data collection method in this study used tests and questionnaires. The data analysis technique used is to analyze data from test scores.Key Words: Gairaigo, Ability, Understanding